An RFID prototype providing industrial security features in the manufacturing environment. (18th November 2009) - Ruz, Mario L.; Vazquez, Francisco
This paper presents the first study of application of the RFID technology as industrial security method. On the basis of a Series 2000 reader of Texas Instrument, a Printed Circuit Board (PCB) prototype has been designed using a Microchip microcontroller, which handles a serial communication with the reader. Its assembled code has been developed and simulated under MPLAB 7.51. A design methodology for inductive coupling antennas considering its geometry and dimensions has been established. The susceptibility of RFID technology in metallic environments has required some tests to achieve an optimal performance of the antenna. On the basis of these studies, the possibilities that RFID presents as automatic security device are evaluated, exploiting the capacity of auto-identification to stop an operation, when a risky situation is presented.